(untitled) - Craddock, Maggie (Massachusetts, 2011)
The book outlines a process for avoiding your type’s signature destructive reflexes and replacing them with new behaviors—helping you to interact productively with other people in the office.
Keywords: Management,Quản lý; Psychological aspects.,Khía cạnh tâm lý